ISPC Commentary on the Revised Proposal for CRP3.4 - November 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the revised proposal for CRP 3.4: Roots, tubers and bananas for food security and income (Revision of September 2011).